2013
DOI: 10.1007/s12010-012-0083-0
|View full text |Cite
|
Sign up to set email alerts
|

Precursor Supply Strategy for Tetramethylpyrazine Production by Bacillus Subtilis on Solid-State Fermentation of Wheat Bran

Abstract: Tetramethylpyrazine (TTMP) is a widely used flavoring additive with a nutty and roasted taste. Solid-state fermentation (SSF) of wheat bran for producing TTMP was studied with Bacillus subtilis CCTCC M208157, which was an exogenous precursor-independent TTMP-producing strain. Factors influencing endogenous precursor supply and TTMP formation in this strain were investigated. According to the findings, glucose and diammonium phosphate contributed to TTMP production but excess salts caused an inhibition on cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…Bacillus species can also generate volatile compounds such as C 4 compounds, pyrazines, volatile acids, and aromatic and phenolic compounds in the liquor. These provide an improved sensory effect and various health benefits [5,34]. However, the functionality of the Bacillus species in Baiyunbian Daqu requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Bacillus species can also generate volatile compounds such as C 4 compounds, pyrazines, volatile acids, and aromatic and phenolic compounds in the liquor. These provide an improved sensory effect and various health benefits [5,34]. However, the functionality of the Bacillus species in Baiyunbian Daqu requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…During the first step, acetoin was efficiently biosynthesized from glucose. If DAP had been added into the fermentation medium in this step, excess salts would cause serious inhibition of cell growth and acetoin accumulation [24]. A DAP feeding strategy was applied to deal with this problem [13].…”
Section: Comparison Of Tmp Production Methods From Renewable Feedstocksmentioning
confidence: 99%
“…Pharmacological studies have demonstrated the ability of TMP to inhibit platelet aggregation, mediate vasodilation, and enhance coronary blood flow. Besides, this compound is widely employed as a flavor additive in the culinary industry 5,6 , and also used as a standard compound in many other industries 7 .…”
mentioning
confidence: 99%